A Front-End Bridgeless Power Factor Corrector For Electric Vehicle Battery Chargers - Carlos Fischer, Jefferson; Andressa da Silva, Juliana; Rômulo de Novaes, Yales; Vidal Garcia Oliveira, Sérgio (Eletrônica de Potência, 2017)
In this paper, a bridgeless power factor corrector converter is suggested for electric vehicle battery chargers. The converter is applicable as a front-end stage for residential charging, i.e. automotive level 1. It is presented a steady state operation analysis for the proposed converter. It operates in current continuous conduction mode controlled by a voltage outer loop and a current inner loop control strategy. Experimental results were performed for a 1 kW prototype, considering 220 V grid voltage, 400 V dc output voltage, 70 kHz switching frequency, and the control system implemented by the UCC28070. The experimental results are satisfactory, which demonstrate a peak efficiency of 98.4% at half load, and features high efficiency from light load to full load. Additionally, the input current THD is less than 5% from half to full load and the power factor is higher than 0.99 from half to full load.